FEATURES OF DEVELOPMENT OF MODERN BANKING SYSTEMS (American Journal of Business Management, Economics and Banking, 2023)
This article examines the main trends in the development of the banking system of the countries of the world, various features of their functioning and modernization. Here, both the general directions of transformation and its individual elements are noted. It can be seen that all of the above changes taking place in the banking system are aimed at automating and digitalizing the processes of banking activities and improving the quality of services provided to customers.